Effects of Copper Oxide Addition on the Electrochemical Properties of Samarium Doped Ceria Electrolyte for Intermediate Temperature Solid Oxide Fuel Cells. (2nd June 2015) - Toor, Sannan Yousaf; Croiset, Eric
Abstract : Low temperature sintering of samarium doped ceria (Sm0.2 Ce0.8 O1.9, SDC) can help in incorporation of metal as a support in low temperature solid oxide fuel cells. Sintering aids (mostly transition metal oxides) can be used to substantially reduce the sintering temperature which also has an effect on the overall electrochemical process. Here, 0-10 mol% of copper oxide is added to the ceria solid solution through glycine nitrate combustion process and sintered at different temperatures ranging between 1000 and 1450°C. Hebb-Wagner polarization method and Electrochemical Impedance Spectroscopy (EIS) are used to separately characterize total, ionic and electronic conductivities. Results show that the 5% CuO/SDC sintered at 1100°C leads to similar total conductivity as pure SDC sintered at 1450°C, while reducing by about one-third the electronic conductivity, which is expected to contribute to reducing the mixed ionic/electronic nature of the SDC electrolyte.